2012
DOI: 10.1097/gme.0b013e3182364e80
|View full text |Cite
|
Sign up to set email alerts
|

Effects of excess body mass on strength and fatigability of quadriceps in postmenopausal women

Abstract: Our results show that despite reduced muscle force, the combination of obesity and postmenopause may be associated with greater resistance to muscle fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 43 publications
2
24
1
10
Order By: Relevance
“…Our data concur with some studies that reported a faster voluntary isometric strength loss and a lower endurance of the upper limb muscles in obese compared to non-obese individuals (Cavuoto and Nussbaum 2014;Mehta and Cavuoto 2015). However, other studies did not observe any difference of fatigue between non-obese and obese people (Maffiuletti et al 2008;Minetto et al 2013;Paolillo et al 2012). For instance, Maffiuletti et al (2008) showed no significant difference in the voluntary and stimulated torque decrement of the KE muscles between normal weight and obese adolescent boys after repeated concentric contractions.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our data concur with some studies that reported a faster voluntary isometric strength loss and a lower endurance of the upper limb muscles in obese compared to non-obese individuals (Cavuoto and Nussbaum 2014;Mehta and Cavuoto 2015). However, other studies did not observe any difference of fatigue between non-obese and obese people (Maffiuletti et al 2008;Minetto et al 2013;Paolillo et al 2012). For instance, Maffiuletti et al (2008) showed no significant difference in the voluntary and stimulated torque decrement of the KE muscles between normal weight and obese adolescent boys after repeated concentric contractions.…”
Section: Discussionsupporting
confidence: 87%
“…While Maffiuletti et al (2007) reported a greater voluntary torque decrement of the KE muscles in 25-year-old obese men (BMI: 41 kg m −2 ) as compared to their normal weight counterparts; these authors also showed no significant difference of muscle fatigue between severely obese (BMI: 34 kg m −2 ) and non-obese adolescent boys (Maffiuletti et al 2008). Furthermore, other authors showed that manifestations of fatigue over the course of repeated contractions of the lower or upper limb muscles were similar (Cavuoto and Nussbaum 2013;Halvatsiotis et al 2002;Minetto et al 2013;Paolillo et al 2012) or lower (Cavuoto and Nussbaum 2014;Mehta and Cavuoto 2015) in obese compared to their normal weight counterparts. Besides, it is still unclear whether the contribution of central and peripheral factors to fatigue is different between non-obese and obese people, since no objective measurement of central vs. peripheral fatigue has been done so far in obese subjects.…”
Section: Introductionmentioning
confidence: 85%
“…Indeed, Levinger et al [27] compared the psychological responses of obese and nonobese subjects to a resistance training session and reported no significant difference of subjective fatigue scores between obese and lean women but a higher fatigue score (i.e., higher fatigability) in lean male subjects as compared to their obese counterparts, which is contradictory to the results of Sartorio et al [25]. Nevertheless, the results reported for women are consistent with those of Paolillo et al [28] who recently compared the fatigability of normal-weight and obese women and did not observe any significant difference in work decrement over the course of a 1-min set of voluntary concentric knee extensions.…”
Section: Impact Of Obesity On Muscle Fatiguecontrasting
confidence: 57%
“…This is important since the aging process induces a loss of muscle mass due to atrophy and neuromuscular degeneration [41]. The bigger muscle mass in the obese postmenopausal women can be influenced by weightbearing effects, which improves muscular function [22].…”
Section: Discussionmentioning
confidence: 99%
“…The systolic blood pressure (SBP) and the diastolic blood pressure (DBP) were measured at rest and at each step of the test using the auscultatory sphygmomanometer. Estimated maximum oxygen consumption (VO 2 max) achieved at peak exercise [22] was determined using the method described by the American Heart Association [23]. The metabolic equivalents (METs) were determined by the formula: VO 2 / 3.5 [23].…”
Section: Assessment Of Biochemical Examsmentioning
confidence: 99%